(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2013)
The argument of fiction with respect to spectators’ illusion is very vast. This paper outlines the interconnection between two particular issues of this immense area of study, which pertain to two paradoxical effects of fiction: (1) the spectator’s cognitive and emotional illusion induced either by theatrical or by cinematographic representation and (2) the more unclear and long-run effects of such representations on everyday life. Plato’s myth of the cave, and some of Husserl’s ideas about “artistic illusion” awakened through the stage performance, will help in delineating some philosophical aspects of the problem